2020
DOI: 10.3390/genes11070735
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of Pi21 by CRISPR/Cas9 and iTRAQ-Based Proteomic Analysis of Mutants Revealed New Insights into M. oryzae Resistance in Elite Rice Line

Abstract: Rice blast (Magnaporthe oryzae) is a devastating disease affecting rice production globally. The development of cultivars with host resistance has been proved to be the best strategy for disease management. Several rice-resistance genes (R) have been recognized which induce resistance to blast in rice but R gene-mediated mechanisms resulting in defense response still need to be elucidated. Here, mutant lines generated through CRISPR/Cas9 based targeted mutagenesis to investigate the role of Pi21 agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

4
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 75 publications
2
19
0
Order By: Relevance
“…Loss-of-function of Pi21 , a quantitative resistance gene encoding a proline-rich protein that includes a putative heavy metal-binding domain and putative protein-protein interaction motifs, results in non-race specific and durable blast resistance (Fukuoka et al 2009 ). Protein profiling of a Pi21 -knockout mutant in the absence of pathogen infection revealed the accumulation of photosynthates, carbohydrate metabolites, and small molecule metabolites, compared with the WT plants (Nawaz et al 2020 ). Additionally, metabolomics studies have shown that the enhanced basal resistance associated with loss-of-function of WRKY62 and WRKY76 (dsOW62/76) is associated with the accumulation of amino acids, constituents of TCA, phenolic acids derived from the phenylpropanoid pathway, upregulated SA and JA, and antimicrobial phytoalexins, such as sakuranetin and phenolamides (Liang et al 2017 ).…”
Section: Proteomics and Metabolomics Studies In Mutants With Altered mentioning
confidence: 99%
“…Loss-of-function of Pi21 , a quantitative resistance gene encoding a proline-rich protein that includes a putative heavy metal-binding domain and putative protein-protein interaction motifs, results in non-race specific and durable blast resistance (Fukuoka et al 2009 ). Protein profiling of a Pi21 -knockout mutant in the absence of pathogen infection revealed the accumulation of photosynthates, carbohydrate metabolites, and small molecule metabolites, compared with the WT plants (Nawaz et al 2020 ). Additionally, metabolomics studies have shown that the enhanced basal resistance associated with loss-of-function of WRKY62 and WRKY76 (dsOW62/76) is associated with the accumulation of amino acids, constituents of TCA, phenolic acids derived from the phenylpropanoid pathway, upregulated SA and JA, and antimicrobial phytoalexins, such as sakuranetin and phenolamides (Liang et al 2017 ).…”
Section: Proteomics and Metabolomics Studies In Mutants With Altered mentioning
confidence: 99%
“…CRISPR/Cas9 can be used to precisely edit target genes to achieve the desired mutations and has higher mutagenesis efficiency and significance than other gene editing technologies [ 1 , 14 ]. CRISPR-Cas9 technology has been vastly used and made remarkable progress in the plant genome editing for improving agronomic traits, plant protection, grain yield, and abiotic stress tolerance [ 1 , 6 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Recently, CRISPR-Cas9-guided SRL1 and SRL2 mutagenesis resulted in improved drought tolerance in rice at the seedling and mature stage [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The targeted and effective gene mutations have been successfully achieved by the CRISPR/Cas9 (clustered regularly interspaced short palindromic repeats/CRISPR-associated protein 9) system in rice for improving the existing varieties and to develop new mutant lines by targeting one or multiple genes [ 23 , 24 , 25 ]. CRISPR/Cas9 is a tremendous technique for precise and targeted editing of the genome of plants and animals.…”
Section: Introductionmentioning
confidence: 99%